Experimental verification of pedagogical conditions for formation of values and semantics experience among future foreign philology specialists in the process of professional training - Lilya Svyshch (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
The current socio-cultural situation actualizes special attention to values, value orientations and other axiological phenomena that comprise axiological knowledge. The rapidly changing world, and therefore the change of axiological guidelines, is a fundamental issue for higher education. This argues the need for special attention to axiological problems in the context of the organization of higher education, in particular the training of future specialists in foreign philology. It has become more relevant because the Standard of Higher Education of Ukraine for the first (bachelor's) level, field of knowledge 03 Humanities, specialty 035 "Philology" does not actually provide any value component of professional training for future professionals. The research hypothesis is based on the thesis that special value-oriented pedagogical conditions in the process of professional training are a prerequisite for the acquisition of values and semantics experience of future specialists in foreign philology, which creates important prerequisites for the formation of axiological competencies. The proposed study is aimed at determining the level of formation of values and semantics experience among future specialists in foreign philology at the initial and final stages of the experiment. The paper shows the methods that allow to achieve this goal and have practically confirmed the formulated research hypothesis.